Correlation for the Sauter Mean Diameter of a Prefilmer Airblast Atomizer at Varying Operating Conditions. Issue 3 (13th September 2016) - Volz, Melanie; Habisreuther, Peter; Zarzalis, Nikolaos
Abstract: One of the key factors that affect the combustion performance in gas turbines and therefore the amount of pollutant emission and the efficiency is the atomization quality of the liquid fuel. Often reliable droplet size distributions for combustion simulations are missing. In this work a correlation for the Sauter mean diameter based on energy equilibrium is derived and compared to results from three‐dimensional numerical simulation of the atomization of a liquid film and to an empirical correlation from the literature. It is shown that the derived correlation agrees better with the results of the simulations than the empirical correlation. Abstract : Often reliable droplet size distributions for combustion simulations are missing due to limitations in measurement techniques. A correlation based on an energy equilibrium is derived and compared to results from numerical simulations and a correlation from the literature to deliver better boundary conditions.